Differences in Image Information on Abdominal CT Scan with Clinical Intra-Abdominal Tumors Between Variations in ASiR-V 60%, 70%, and 80% - Desta Putri Arkhamah; Supriyadi Supriyadi; Fani Susanto; Hernastiti Sedya Utami; Lutfatul Fitriana (Poltekkes Kemenkes Tanjung Karang, 2026)
Previous studies have shown that an ASiR-V rate of 60% is optimal for contrast-enhanced abdominal CT scans in patients with kidney stones. In this study, however, the ASiR-V variations tested were 60%, 70%, and 80%, with a focus on clinical intra-abdominal tumors. The objective was to measure the optimal signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) values for CT images of these tumors. The research employed a quantitative retrospective experimental design with a sample of 10 patients who met the inclusion criteria. The findings reveal notable differences in SNR, CNR, and Hounsfield Unit (HU) values across the ASiR-V variations, with the 70% ASiR-V showing the highest values for both SNR and CNR.